2021
DOI: 10.3390/jcm10235704
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Xanthoma Is Related to the Rapid Growth of Gastric Cancer

Abstract: Early detection of gastric cancer is important. However, rapid growth of gastric cancers that cannot be resected endoscopically occurs even with periodic check-ups. Accordingly, we assessed factors associated with the speed of gastric cancer growth by examining historical endoscopic images. A total of 1996 gastric cancer cases were screened, and characteristics of lesions with slow and rapid growth were assessed. A total of 114 lesions from 114 patients were included in the assessment. Sixty slow-growing and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…Histopathological confirmation of xanthomas is needed to rule out malignancy. This is especially true given its association with cancer; it has also been shown that gastric xanthomas are a factor related to the rapid growth of gastric cancer [ 3 ]. This case highlights the necessity of searching for accompanying premalignant lesions when a gastric xanthoma is discovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological confirmation of xanthomas is needed to rule out malignancy. This is especially true given its association with cancer; it has also been shown that gastric xanthomas are a factor related to the rapid growth of gastric cancer [ 3 ]. This case highlights the necessity of searching for accompanying premalignant lesions when a gastric xanthoma is discovered.…”
Section: Discussionmentioning
confidence: 99%
“…While immunosuppression has been suggested as a possible risk factor for gastric xanthomas, there has been no cited evidence in the literature about how it might be correlated [ 2 ]. There is emerging evidence that gastric xanthomas could be useful markers for predicting the development and location of early gastric cancer, and they can sometimes also be associated with dyslipidemia [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Це узгоджується з результатами Sekikawa et al (2016) та інших дослідників, які свідчать про те, що пацієнти з ксантомами мали більш поширений атрофічний гастрит, ніж пацієнти без них [16]. У цілому авторами було виявлено кореляцію між вираженістю й поширеністю атрофії СО шлунка і наявністю ксантом [2,5,15,17,19].…”
Section: рисунок 9 -хворий б 75 років: а) ендоскопія в білому світлі:...unclassified
“…Існує низка робіт про взаємозв'язок між ксантомами й раком шлунка [4,9,13]. Sekikawa et al (2013) серед пацієнтів з атрофічним гастритом діагностували рак шлунка суттєво частіше в осіб із ксантомами, ніж без них [5,15,16]. Ці результати підтверджено і в роботі K. Yamashita et al (2019), автори припускають, що ксантоми можуть бути корисним ендоскопічним індикатором ризику раку шлунка [2].…”
Section: рисунок 9 -хворий б 75 років: а) ендоскопія в білому світлі:...unclassified
“…In recent years, increased attention has been paid to gastric cancer cases detected after eradication, including those occurring after eradication and those occurring before but detected after Hp eradication, with a particular focus on cases detected more than a year after Hp eradication [7] . Several studies have identi ed map-like redness (MLR) as an independent risk factor for gastric cancer after Hp eradication [8][9][10][11] . The manifestations of MLR (also called "color reversal" phenomenon or mottled patchy erythema [MPE]) result from Hp-associated gastritis or Hp-associated highly atrophic gastritis, with improvements following Hp elimination through the use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%